AHP 21: A Space for the Possible: Globalization and English Language Learning for Tibetan Students in China - Rebecca A, Clothey (Asian Highlands Perspectives, 2018)
With growth in China's tourist industry and international trade in recent decades, learning English has become a threshold for determining who can get what others cannot. There are many opportunities to master and become culturally competent in English in the prosperous urban and eastern coastal areas where foreign businesses and tourists are common. Disparities between east and west, urban and rural, and majority and minority areas continue to widen in China, raising the question of how to increase economic development in more remote rural communities. Meanwhile, how minority cultures might remain resilient amid the forces of globalization is a continuing concern. The tensions between globalization, development, and cultural identity as illustrated through an English language program for Tibetan speakers in one of China's poorest provinces, Qinghai, are described.